SCREENING FOR HEPATOCELLULAR CARCINOMA IN CHRONIC LIVER DISEASE: A SYSTEMATIC REVIEW - Ardena Lianto, Lie Milka (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Chronic liver disease is the most significant risk factors for the development of hepatocellular carcinoma (HCC). High-risk patients should undergo routine screening for HCC, but it is unclear how much data there is to support this suggestion. The aim: This study aims to determine the screening options for hepatocellular carcinoma in chronic liver disease. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and ScienceDirect, were used to do this. It was decided not to take into account review pieces, identical works that had already been published, or works that were only half done. Results: In the PubMed database, the results of our search brought up 110 articles, whereas the results of our search on ScienceDirect brought up 285 articles. The results of the search conducted by title screening yielded a total 29 articles for PubMed and 15 articles for ScienceDirect. We compiled a total of 6 papers, 2 of which came from PubMed and 4 of which came from ScienceDirect. We excluded 1 review article. In the end, we included five research that met the criteria.